Refractive error, axial length, and relative peripheral refractive error before and after the onset of myopia - Mutti, Donald O; Hayes, John R; Mitchell, G Lynn; Jones, Lisa A; Moeschberger, Melvin L; Cotter, Susan A; Kleinstein, Robert N; Manny, Ruth E; Twelker, J Daniel; Zadnik, Karla (Investigative ophthalmology & visual science, 2007)
To evaluate refractive error, axial length, and relative peripheral refractive error before, during the year of, and after the onset of myopia in children who became myopic compared with emmetropes. Subjects were 605 children 6 to 14 years of age who became myopic (at least -0.75 D in each meridian) and 374 emmetropic (between -0.25 D and +1.00 D in each meridian at all visits) children participating between 1995 and 2003 in the Collaborative Longitudinal Evaluation of Ethnicity and Refractive Error (CLEERE) Study. Axial length was measured annually by A-scan ultrasonography. Relative peripheral refractive error (the difference between the spherical equivalent cycloplegic autorefraction 30 degrees in the nasal visual field and in primary gaze) was measured using either of two autorefractors (R-1; Canon, Lake Success, NY [no longer manufactured] or WR 5100-K; Grand Seiko, Hiroshima, Japan). Refractive error was measured with the same autorefractor with the subjects under cycloplegia. Each variable in children who became myopic was compared to age-, gender-, and ethnicity-matched model estimates of emmetrope values for each annual visit from 5 years before through 5 years after the onset of myopia. In the sample as a whole, children who became myopic had less hyperopia and longer axial lengths than did emmetropes before and after the onset of myopia (4 years before through 5 years after for refractive error and 3 years before through 5 years after for axial length; P < 0.0001 for each year). Children who became myopic had more hyperopic relative peripheral refractive errors than did emmetropes from 2 years before onset through 5 years after onset of myopia (P < 0.002 for each year). The fastest rate of change in refractive error, axial length, and relative peripheral refractive error occurred during the year before onset rather than in any year after onset. Relative peripheral refractive error remained at a consistent level of hyperopia each year after onset, whereas axial length and myopic refractive error continued to elongate and to progress, respectively, although at slower rates compared with the rate at onset. A more negative refractive error, longer axial length, and more hyperopic relative peripheral refractive error in addition to faster rates of change in these variables may be useful for predicting the onset of myopia, but only within a span of 2 to 4 years before onset. Becoming myopic does not appear to be characterized by a consistent rate of increase in refractive error and expansion of the globe. Acceleration in myopia progression, axial elongation, and peripheral hyperopia in the year prior to onset followed by relatively slower, more stable rates of change after onset suggests that more than one factor may influence ocular expansion during myopia onset and progression.